(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
The main goal of our study was to develop a cell culture based vaccine model for equine influenza virus and within the purpose, a total of 161 equine nasal swabs were collected to detect the equine influenza virus and 15 (9.3%) samples were tested as positive with haemagglutination test (HA assay). From these positive swabs, equine influenza virus (EIV) was inoculated in Madin-Darby Canine Kidney (MDCK) cell line. The infected cell-culture fluid was inactivated with 2-Bromoethylamine Hydrobromide and mixed with MONTANIDE ISA 206 oil-based adjuvant (acid) at ratio 1: 1. The purity, toxicity, viscosity, stability, and activity of the newly prepared vaccine model was analyzed. According to our experimental results, the vaccinated horse developed an antibody titer against equine influenza 1:64-1: 128 at 30 days after the first injection, and the titer was increased at 1: 128-1: 256 at 60 days after the first injection and gradually decreased to 1: 16-1:32 at 180 days. These results showed that the vaccine model is active for 6 months. Адууны томуу өвчний эсийн өсгөвөрт вакцины загвар бэлтгэн туршсан дүн Бидний судалгааны ажлын гол зорилго нь адууны томуу өвчний эсийн өсгөвөрт вакцины загвар гарган авах бөгөөд зорилгын хүрээнд адууны томуу өвчний нутгийн үүсгэгчийг илрүүлэхээр нийт 161 адууны хамрын арчдас цуглуулж, цус наалдуулах урвалаар шалгахад 15(9.3%) дээж эерэг дүн үзүүлсэн. Эдгээр эерэг дүн үзүүлсэн арчдаснаас MDCK дамжмал эсийн өсгөвөрт халдвар хийв. Хураан авсан эмгэгт шингэнийг 2-Bromoethylamine Hydrobromide бодисоор идэвхгүйжүүлээд, MONTANIDE ISA 206 тосон суурьт адьювант (хүчлүүр) бодистой 1:1 харьцаатай хольж вакцины загварыг бэлтгэсэн. Бэлтгэсэн вакцины загварын ариун чанар, хорон чанар, зуурамтгай байдал, тогтвортой байдал болон идэвхит чанарыг шалгалаа. Бидний хийсэн туршилтын дүнгээс үзвэл вакцин таригдсан адууны анхны тарилтын дараа 30 хоногтоо 1.64-1:128 таньцтай дархлаа тогтсон бөгөөд 60 дахь хоногтоо 1:128-1:256 таньцтай болж хадгалагдан тэр нь аажмаар буурч 180 хоногтоо 1:16-1:32 таньцтай болсон байна. Үр дүнгээс харахад бидний бэлтгэсэн вакцины загвар нь 6 сарын хугацаанд хамгаалах идэвхитэй байна. Түлхүүр үг: Томуу, вирус, MDCK эс , вакцин